IMPACT OF HUMAN RESOURCES INFORMATION SYSTEM ON HUMAN RESOURCE STRATEGIES WITH EMPIRICAL STUDY OF BANKING INDUSTRY (Journal of Pharmaceutical Negative Results, 2023)
This paper highlights the impact of human resource information system with human resource strategies. HRIS is a kind of tool which is designed to meet the core need of business which automatically fulfil the requirements and needs of both managers and employees. As this paper highlights the human resource information system with the banking industry, on one side banking industries are adapting the software for the betterment of their employees but on the other side still people in the banking industry have the resistance towards the accepting of this software. Thus, in today’s scenario organisation motive is to build up the morale of their employees and get them familiar with the new technologies which automatically give the best result to the organisation. This study of research paper gives the glimpse of some banking sector who already adapted the technology.This paper focus on the employees about why they have resistance in adapting the new tech software.